Pengaruh Disiplin Kerja, Motivasi Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT Dunia Rajawali Makmur Batam - Keni , Oswin Sasa; Sanga , Laurensius Dihe; Dabur , Feliks (Tractare: Jurnal Ekonomi-Manajemen, 2025)
This study aims to determine the effect of work discipline, work motivation and work environment on employee performance at PT Dunia Rajawali Makmur Batam both partially and simultaneously. The type of research applied in this study is quantitative research, the population in this study was 32 respondents. The researcher used a saturated sampling technique with 31 respondents. The data collection technique used a questionnaire and was distributed via google form. The researcher used data analysis using SPSS version 26. The results of the study found that the work discipline variable had a t count of 3.933 > t table 1.696 and a significance value of 0.001 < 0.05, so H0 was rejected and Ha was accepted, the work motivation variable had a t count of 3.866 > t table 1.696 and a significance value of 0.013 < 0.05, so H0 was rejected and Ha was accepted, the work environment variable had a t count of -2.280 > t table 1.696 and a significance value of 0.031 < 0.05, so H0 was rejected and Ha was accepted. The three variables, namely work discipline, work motivation and work environment together have an F count of 6,816, F table > 2.91 and a significant value of 0.001 < 0.05. This shows that simultaneously work discipline, work motivation and work environment have a positive and significant effect on employee performance at PT Dunia Rajawali Makmur Batam. And the coefficient of determination (R2) shows that the independent variables contribute 43.1% while the remaining 56.9% is influenced by other factors not examined in this study.